1991
DOI: 10.1620/tjem.163.149
|View full text |Cite
|
Sign up to set email alerts
|

Gossypol effects on monoamine oxidase(MAO) activity in several organs of term rats.

Abstract: In order to study the effect of gossypol on the monoamine oxidase (MAO) activity in pregnant rat organs, 20 day pregnant rats were sacrificed, and MAO activity/0.02 g tissue of several organs and total MAO activity/organ, were determined. The control group (n-5) were injected with vehicle intramuscularly on the 17th, 18th and 19th day of pregnancy, and the gossypol treated group (n 4) were injected with gossypol acetic acid (GAA) (25 mg/kg of body weight) intramuscularly on the 17th, 18th and 19th day and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The results show that, during the prenatal period, the placenta and fetal brain are the most metabolically active organs in 5-HT degradation by MAO, followed by the intestine, lungs, and liver. These findings correspond well with reports by other groups for rats and humans, where placental MAO-A activity exceeds that of the lungs and liver [ 50 , 51 ]. Consequently, the interplay between placental and fetal MAO activity seems fundamental for regulating 5-HT circulating levels in the fetoplacental unit and wiring the placenta–brain axis for proper neurodevelopment of the fetus.…”
Section: Discussionsupporting
confidence: 93%
“…The results show that, during the prenatal period, the placenta and fetal brain are the most metabolically active organs in 5-HT degradation by MAO, followed by the intestine, lungs, and liver. These findings correspond well with reports by other groups for rats and humans, where placental MAO-A activity exceeds that of the lungs and liver [ 50 , 51 ]. Consequently, the interplay between placental and fetal MAO activity seems fundamental for regulating 5-HT circulating levels in the fetoplacental unit and wiring the placenta–brain axis for proper neurodevelopment of the fetus.…”
Section: Discussionsupporting
confidence: 93%
“…Huang and Wang (1994) reported the effects of Gossypol on testosterone secretion. They have noticed a decrease in testosterone secretion, which was attributed to the contribution of adrenergic receptor inhibition in the hypothalamus by Gossypol this adrenergic receptor inhibition might decrease GnRH which leads to decrease of LH-Testosterone axis (Kono et al, 1991) Furthermore Leydig cell secretion act on the hypothalamus and pituitary gland through regulating the negative feedback mechanism of the quantity of GnRH release (West, 1982). Hul et al (1993); Comhaire (1994) Huang and wang (1994) and Zhaang et al (1994) reported that the mechanism of testosterone and estrogen releas was disrupted by Gossypol, through inhibition of hypothalamic estrogen receptor.…”
Section: Discussionmentioning
confidence: 99%